Do reusables pose greater infectious risks than disposables for consumer goods? A systematic literature review - Ira, Sanjidah Ahmed; Sherry, Brooke Elise; Amin, Ruhana; Abdul-Hamid, Ma-sum; Roberts, Timothy; Hochman, Sarah; Thiel, Cassandra L. (International Journal of Infection Control, 2024)
Increased concern over climate change and the emergence of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) virus resulted in a clash of political directives around reusable and disposable food serviceware. Decreasing single-use items will likely reduce consumption and environmental emissions; however, improper cleaning of reusable items could result in greater risks of disease transmission. We sought to assess the risks of reusable and disposable food serviceware and document disinfection protocols by conducting a systematic literature review of articles that assessed materials or products that could be fomites to specific food-borne pathogens. After initial screening, the study team extracted data from 122 articles. The most common pathogens studied were E. coli (25% of included studies), general bacteria (24%), and Norovirus (16%). Thirteen studies (8%) focused on SARS-CoV-2. A majority of studies analyzed plastics (27%), stainless steel (22%), or porous surfaces such as paper and cardboard (12%). Forty seven of the studies (35%) were conducted in a food service setting, and 40 studies (30%) tested disinfection techniques. Despite a large body of related literature, there is very little evidence suggesting that either reusable or disposable food serviceware is safer for minimizing infectious risks. Pathogens can survive on various fomites, though greater surface porosity and higher humidity levels increase viability of most pathogens. There appear to be no major differences in pathogen viability on various fomites. There is a paucity of research that can specifically aid in developing policy or guidelines for appropriate use of reusable food serviceware. Though given recent studies on SARS-CoV-2, banning reusable bags and food serviceware is an inappropriate response to this particular pathogen, which is rarely spread through surface contact. Further research is needed that explicitly studies pathogen viability, transmission risks, and appropriate disinfection techniques for disposable and reusable food serviceware in order to devise effective sustainability policies.